(untitled) (Nepal Medical College Journal, 2025)
Pediatric constipation is one of the common gastrointestinal conditions in children presenting with varying complains which are easy to detect from history, but the condition is often under diagnosed. It has significant impact on daily life troubling the children and their parents with complains like hard and painful defecation, abdominal pain, voluntary stool retention and blood in stool. Prevalence of constipation has been found in wide variation among studies from multiple western as well as Asian countries, but there are no studies from Nepal. This cross-sectional study was conducted at our center including children from 2-14 years of age presenting to pediatric OPD. Children were diagnosed by using ROME IV criteria for constipation and analyzed for demographic profile, presenting symptoms, socio-economic conditions, psychological aspects and dietary habits. Out of total 400 children, 127 (31.8%) had constipation with slight male predominance (M:F=1.2:1). Most constipated children had Bristol type I and type II stool with frequency ≤3 episodes per week. Most common complaint was passage of hard stool (88.2%) and painful defecation (52.8%). Outdoor toilet facility was one of the predisposing factors and aversion to use school toilet was the most common precipitating psychological factor. Increased fruits and vegetables intake reduced its incidence and predominant cow’s milk intake increased it. Thus constipation is not an uncommon condition among Nepali children and it is associated with different feeding habits and psychosocial factors. The increased intake of high fiber diet along with availability of indoor toilets reduces the risk of constipation in children.